The Impact of Obesity on the Management and Outcomes of Postpartum Hemorrhage - Polic, Aleksandra; Curry, Tierra L.; Louis, Judette M. (American Journal of Perinatology, 2020)
Objective The study aimed to evaluate the impact of obesity on the management and outcomes of postpartum hemorrhage.Study Design We conducted a retrospective cohort study of women who delivered at a tertiary care center between February 1, 2013 and January 31, 2014 and experienced a postpartum hemorrhage. Charts were reviewed for clinical and sociodemographic data, and women were excluded if the medical record was incomplete. Hemorrhage-related severe morbidity indicators included blood transfusion, shock, renal failure, transfusion-related lung injury, cardiac arrest, and use of interventional radiology procedures. Obese (body mass index [BMI] ≥ 30 kg/m2) and nonobese women were compared. Data were analyzed using Chi-square, Student's t-test, Mann–Whitney U test, and linear regression where appropriate. The p-value <0.05 was significant.Results Of 9,890 deliveries, 2.6% (n = 262) were complicated by hemorrhage. Obese women were more likely to deliver by cesarean section (55.5 vs. 39.8%, p = 0.016), undergo a cesarean after labor (31.1 vs. 12.2%, p = 0.001), and have a higher quantitative blood loss (1,313 vs. 1,056 mL, p = 0.003). Both groups were equally likely to receive carboprost, methylergonovine, and misoprostol, but obese women were more likely to receive any uterotonic agent (95.7 vs. 88.9%, p = 0.007) and be moved to the operating room (32.3 vs. 20.4, p = 0.04). There was no difference in the use of intrauterine pressure balloon tamponade, interventional radiology, or decision to proceed with hysterectomy. The two groups were similar in time to stabilization. There was no difference in the need for blood transfusion. Obese women required more units of blood transfused (2.2 ± 2 vs. 2 ± 5 units, p = 0.023), were more likely to have any hemorrhage-related severe morbidity (34.1 vs. 25%, p = 0.016), and more than one hemorrhage related morbidity (17.1 vs. 7.9, p = 0.02). After controlling for confounding variables, quantitative blood loss, and not BMI was predictive of the need for transfusion.Conclusion Despite similar management, obese women were more likely to have severe morbidity and need more units of blood transfused.Key Points
Keywords: maternal morbidity; maternal mortality; obstetric hemorrhage; postpartum; obesity; blood transfusion